2018
DOI: 10.1016/j.cub.2018.07.073
|View full text |Cite
|
Sign up to set email alerts
|

Visual Detection and Avoidance of Pathogenic Bacteria by Aphids

Abstract: Highlights d Pea aphids avoid feeding on leaves with pathogenic bacteria on their surface d Pea aphids use vision in the presence of ultraviolet light to avoid pathogenic bacteria d Avoidance is mediated by visual detection of fluorescence from bacterial pyoverdine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…insects can detect pathogens and avoid them [7], it remains unclear whether social insects can reliably detect pathogens at a potential nesting site and avoid them. Queens of wood ant were attracted to fungal pathogens during the initial stage of colony founding [8].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…insects can detect pathogens and avoid them [7], it remains unclear whether social insects can reliably detect pathogens at a potential nesting site and avoid them. Queens of wood ant were attracted to fungal pathogens during the initial stage of colony founding [8].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…In particular, for social insects that nest in soil, pathogens are a significant danger that varies greatly from place to place [ 3 6 ]. Though some insects can detect pathogens and avoid them [ 7 ], it remains unclear whether social insects can reliably detect pathogens at a potential nesting site and avoid them. Queens of wood ant were attracted to fungal pathogens during the initial stage of colony founding [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that aphids can become infected from epiphytic bacteria on leaf 189 surfaces (Stavrinides et al 2009;Hendry et al 2018). Consequently, we hypothesized that the 190 mortality of aphids feeding on epiphytically infected plants should be similar to that which we see 191 when feeding bacteria suspended in artificial diet to aphids, yet likely take longer to achieve as 192 aphids would be less likely to become rapidly or heavily infected.…”
Section: Impact Of Aphid Presence On Plants 164mentioning
confidence: 99%
“…Along with chemical contributions to floral phenotype, microbes can modify the visual characteristics of flowers directly (e.g. potentially as a result of pigment production or fluorescence from bacterial pyoverdine; Hendry et al ., ) or indirectly (e.g. by inducing changes in petal colors or their longevity; Engelhard, ; Jennersten, ).…”
Section: Floral Extended Phenotypementioning
confidence: 99%